Graph-analytical models of complex systems for state assessment “organism – environment” - Kozulia, T.V.; Kozulia, M.M. (Problems of Atomic Science and Technology, 2022)
Practicism in business is generally associated with obtaining high-performance goal-setting solutions. Cost reduction in the case of making a decision requires weight components identification in the object “state (environment) - system processes - system end state” associated with the structure or functionality of systems (processes), which themselves arbitrarily determine the target result. The works aim is to determine model type of a complex structured object of any purpose, which adequately reflects system state and interaction with the environment “(environment – system) – process – (system state – environment)” in a situation of varying degrees uncertainty. Assessment of systemic formation state is due to the grouping of methods, their complex application in the study of the interaction “system – environment”, which is determined by the corporative relations between the components. To solve the problem of quality assessment of such system objects, structural and graphical approach information and methodological support was offered as a set of methods.